2003
DOI: 10.1093/geronb/58.2.p112
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Stressors and Uplifts of Caregiving With Caregiver Burden and Depressive Mood: A Meta-Analysis

Abstract: In the present meta-analysis, we integrated findings from 228 studies on the association of six caregiving-related stressors and caregiving uplifts with burden and depressed mood. Care recipients' behavior problems showed stronger associations with caregiver outcomes than other stressors did. The size of the relationships varied by sample characteristics: Amount of care provided and care receivers' physical impairments were less strongly related to burden and depression for dementia caregivers than for caregiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

83
794
1
28

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 919 publications
(939 citation statements)
references
References 226 publications
83
794
1
28
Order By: Relevance
“…These stressors range from having to perform daily self-care tasks, such as bathing and feeding, to coping with adverse problem behaviours, such as wandering off and becoming disorientated in the environment. 10,11 In two studies it emerged that dementia patients' behavioural problems were one of the most important factors contributing to caregiver burden, with aggression being singled out as the critical symptom that is most often associated with burden. 12−14 It has been postulated that burden occurs as a result of the continuous vigilance that must ensue as a result of these other related behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…These stressors range from having to perform daily self-care tasks, such as bathing and feeding, to coping with adverse problem behaviours, such as wandering off and becoming disorientated in the environment. 10,11 In two studies it emerged that dementia patients' behavioural problems were one of the most important factors contributing to caregiver burden, with aggression being singled out as the critical symptom that is most often associated with burden. 12−14 It has been postulated that burden occurs as a result of the continuous vigilance that must ensue as a result of these other related behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…(13) Although BPSD are composed of wide-ranging symptoms including depression, physical aggression and paranoid delusions, it remains unclear whether specific individual symptoms, or symptom clusters (one or more symptoms grouped together, e.g., mood symptoms) differentially impact caregivers. The majority of research studies that have concluded that BPSD negatively impact caregivers have solely examined cumulative scores of BPSD.…”
Section: Introductionmentioning
confidence: 99%
“…Assistance with ADLs in elderly persons has not been found to be related to poor health conditions among caregivers. Rather, care recipients who have frequent behavioral or emotional problems place more stress on caregivers (Pinquart & Sörensen, 2003;Pruchno & Resch, 1989). …”
Section: Discussionmentioning
confidence: 99%